Enhanced transdermal delivery of ketoprofen from bioadhesive gels - Singh S.; Gajra B.; Rawat M.; Muthu M.S. (My University, 2025)
The aim of this study was to evaluate and compare the in vitro and in vivo transdermal potential of bioadhesive gels of ketoprofen by using gelling polymers like sodium carboxymethylcellulose, xanthan gum, poloxamer 407 and carbopol 934P as bioadhesive polymer with and without penetration enhancer (oleic acid). The effect of oleic acid as a penetration enhancer was examined when it was added to the bioadhesive formulations. Gels were evaluated for bioadhesive force and viscosity. To study the in vitro potential of these formulations, permeation studies were performed with Franz diffusion cell using excised rat abdominal skin. Carrageenan induced rat paw edema model was used to investigate their in vivo performance. The commercial formulation of ketoprofen was used as a reference formulation. The in vitro permeation studies indicate that ketoprofen bioadhesive gel of poloxamer 407 with penetration enhancer was superior to gels of sodium carboxymethylcellulose and xanthan gum with penetration enhancer (oleic acid). The permeation rate of ketoprofen from poloxamer 407 based bioadhesive gel with 15% v/w penetration enhancer was higher (rat abdominal skin flux = 0.421 ± 0.032 mg/cm2/h) than the permeation rate of sodium carboxymethylcellulose and xanthan gum based bioadhesive gel with 15% v/w penetration enhancer. In the paw edema test poloxamer 407 based bioadhesive gel with 15% v/w penetration enhancer showed the best permeation and effectiveness. The in vitro and in vivo studies showed that bioadhesive gels of ketoprofen could be used for effective therapy.